Investigation Effects of Lavenders Flowers Extracts on Catalase Activity and Some Microorganisms. - Abbed, Ali Mohammed (Al-Nahrain Journal of Science, 2019)
The present study was proposed to examine one of the important herbal plant is known Lavender and study the interaction of its extracts with enzymatic oxidation reduction process and anti microorganism. The catalase assay in vitro was implied in this work. Lavender flower containing on essential oils has been many uses for disease treatment, this plant bring from the trading market in Iraq. The current study involved biological activity on two ways; alcoholic extract on enzymatic activity, other way hot water extract and alcoholic extract on four isolate of bacteria and one type fungi. (The weight of flower is equal to 1gm/50ml for two extracts). The results of this study demonstrated effect of lavender to be activator agent of catalase enzymatic activity and Vmax was calculated without and with extract that equal to (88.6, 208)Ku/L and km equal to (53.5, 72.4)mM respectively by Line weaver-Burk plot. The activation percentage was calculated by using different volume of Ethanolic extract, that maximum activation is recorded equal to 133.6% at substrate concentration 60 mM and 100µl alcoholic extract. On the other hand their effects on microorganism obvious in the present study that showed not effect began.